The reconstruction of Arabic language instructional design in higher education: An integrative approach to improve learning quality - Imrob, Kristina; Sobari, Dolla; Abdullah, Muhammad Yahya; Humairoh, Salwa (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
This study addresses how Arabic language instruction is implemented at the State Islamic University (UIN) Raden Fatah Palembang. It explores the application of instructional design based on an integrative approach using a case study and a descriptive qualitative approach. Conducted at the Faculty of Tarbiyah and Teacher Training for four to six months, the research involved 85 students and 11 lecturers through interviews, questionnaires, and document analysis. Data were analyzed using NVivo 12 Pro software. The findings indicated that the Arabic language course has been offered in the first semester for Faculty of Tarbiyah and Teacher Training students (FITK); however, its integration with other study programs remains limited. Some study programs, such as Primary School Teacher Education, Early Childhood Islamic Education, Islamic Education Management, Islamic Religious Education, Mathematics, and Biology, have integrated Arabic. Meanwhile, some others like Chemistry, Physics, and English Education have not applied such integration. Survey results indicated that although 50 out of 85 students have acknowledged the integration efforts, it remains suboptimal in the implementation. This study recommends the development of an integrative, cross-disciplinary Arabic language curriculum at the university to enhance the relevance and engagement of students in applying Arabic according to their academic fields.